Androgenesis and gynogenesis in tomato (Solanum lycopersicum L.) in vitro - A. A. Shergina; A. B. Kurina (Труды по прикладной ботанике, генетике и селекции)
Tomato (Solanum lycopersicum L.) is one of the most consumed vegetable crops worldwide. Tomato fruits are rich in vitamins, minerals, and pigments, including lycopene. The high demand and the need to enhance tomato production call for new improved cultivars and F1 hybrids.Biotechnological methods reduce the time for source material development and the labor intensity of breeding efforts. Obtaining doubled haploid plants makes it possible to fix and analyze new gene combinations faster than with conventional breeding techniques, and produce homozygous genotypes. Tomato is highly unsusceptible to haploid induction, which has been continuously studied for more than 40 years and is still of special interest. The main methods for producing haploids are based on androgenesis and gynogenesis. Androgenesis is the production of haploids from the cells of the male gametophyte, and gynogenesis from the cells of the female gametophyte.The objective was to review the research on the induction of tomato haploids based on androgenesis and gynogenesis. No standardized, efficient or reproducible protocols are currently available to produce doubled haploids of tomato. It is necessary to determine the incubation conditions, physicochemical environments, dependence of the genotype in vitro, physiological state of the donor plant, and development of the anther, which affect the reproducibility of protocols to achieve haploid induction. Anther culture for obtaining haploid tomato plants has not yielded successful results, and the studies on microspore culture were too few, so it is difficult to understand the effectiveness of this technique. The method of gynogenesis is poorly investigated, but the culture of unfertilized ovules can become a successful way to obtain tomato haploids, with more research on this subject.